Global warming: an analysis of the existing Malaysian legislations in curtailing the problem / Siti Khadijah Abdullah Sanek, Nur Irinah Mohamad Sirat and Azlyn Ahmad Zawawi - Abdullah Sanek, Siti Khadijah; Mohamad Sirat, Nur Irinah; Ahmad Zawawi, Azlyn (Research Management Institute, 2012)
Malaysia is one of the signatories of the Kyoto Protocol of the United Nations Framework Convention on Climate Change (UNFCCC). It is an international environmental agreement which targeting on greenhouse gas emissions and fighting global warming. The Kyoto Protocol was initiated at the Third Conference of the Parties in Kyoto, Japan, December 1-11, 1997 and the Parties of the UNFCCC agreed to a historic protocol to reduce greenhouse gas (GHG) among the member countries. As of November 2009, 187 states have signed and ratified the protocol. The purpose of this research is to discover the inadequacy of the current legislations pertaining to global warming issue as compared to the standard of the international conventions. Therefore, suggestion would be made in proposing a viable legislative reform targeting on greenhouse gas emissions reduction. Our research is based on a qualitative research manner and methods. References will also be made to our local statutes as well as the international conventions. This research may form the basis for policy maker’s consideration in formulating a legislation that specifically addresses the matter critically and to provide the information accessible to any potential person or body within the concerns and interests.